TRADEMARK, BRAND, LOGO MANAGEMENT IN THE MARKETING MANAGEMENT SYSTEM IN THE DAIRY INDUSTRY ON THE TERNOPYL MARKET. - VASYLYSHYN, Vladeslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
A brand in a company usually develops from a trademark (trademark) or logo into a trademark (TM) and then into a brand. Brand management should be entrusted to a special team (which would consist of managers, marketers, psychologists, advertisers, sales specialists, neuropsychologists, designers, creative people, dietitians, nutritionists, specialized technologists, doctors, pharmacists). And this can be a permanent team or a variable team or a mix of them. Niche commodity and food brands for commodity companies usually consist of two parts: a material part (quality-functional, in our case quality-taste), which is reflected mainly in the trademark or trademark, and another part - non-material, associated with psychology, neuropsychology and sociology (mainly fashion, image, expectations, benefits). Of the 11 basic marketing laws that can be used in branding, these are: the law of double threat, the law of double threat of customer retention, especially the Pareto law (20/80), the law of natural monopoly, the law of customer loyalty, the law of prototypicality, the law of overlapping customer bases, the law of negative binary Dirichlet distribution, the law of similarity of customer bases of different brands, the law of equalization of customer behavior. Usually in the dairy industry, companies cannot grow up to brands and use the Pareto law, the law of customer loyalty, the law of prototypicality quite often. But they do not use the law of overlapping customer bases, the law of forming a brand image, the law of double threat and other marketing (branding) laws. From the literature on branding, it is known about four main branding strategies: product, customer, market, corporate. In my opinion, the Molokiya company uses only a product strategy, and then TM (logo and possibly TK. It should also be said that there is no clear legislative field for TM and brand in Ukraine, as well as taxation). However, it is branding, even niche, that will give us maximum benefits with minimal effort. It should also be said that there are four additional branding strategies, which partially coincide with the same names in marketing strategies, and these are personal branding of owners, directors and staff; the second type of additional branding strategy is innovative or lateral, which creates new products or even entire lines; the third type of additional branding strategy is distribution through its own networks or other retail chains that may or may not have their own brands for sale; and the fourth additional type of branding strategy is individual sales. In my opinion, practically none of the additional branding strategies are used by the Molokiya company and its competitors in the Ternopil market, although they would lead to the transformation of the TM management strategy into a strategy for creating and managing a brand (of the buyer, the market and the corporation) and the possibility of using all the known laws of marketing, management and branding. In my opinion, there is already a fifth main branding strategy - "green" (i.e. all technology and all products and ingredients are 100% natural) and it should be used by both the Molokiya company and its competitors. When creating, promoting and supporting a brand, you can do this in a rational, irrational and irrational way or technologies. The simplest way is rational using marketing tools (shape, color schemes, signs and symbols) based on the theory of Fibonacci numbers, Archimedes’ golden sections, and the use of traditions, symbols, signs, color schemes and heraldry, vexology, mysticism, etc. of the Ukrainian people. Conducted field research on 12 major producers of fermented milk products and evaluated their trademarks, TMs, brands and theoretical calculations on these issues regarding brand management, came to the conclusion that none of the companies meets the qualitative and quantitative indicators of the brand. Increasingly, in marketing technologies and branding, the introduction and management of new products is used and new products are based on modules, on changing the size, on changing the packaging, on changing the design, on creating additions, innovations on reducing the efforts for opening and consumption, on introducing other components, and for this purpose, super fragmentation of the market can be used. It is also necessary to pay attention to new products that have gone the alternative path of new products using lateral marketing and there are a lot of concepts and lateral shifts here, and this marketing as an addition to vertical marketing. Also, today, in our opinion, to improve communication, there is an urgent need to restore the system built in the 20s on young industry and banking by Cardinal A. Shiptytsky and J. Slipy, including using old technologies and new research and providing jobs in the countryside and improving demography. Of course, for this it is necessary to introduce a special taxation system, or more precisely, a system of investment and support and restoration of private herds of cows, goats, sheep, and so on. even horses, yaks, etc. in small households.